Concentrator Operations At Chino Mines Co. ? Introduction - R. P. Schneider (Society for Mining, Metallurgy & Exploration, 1985)
The Chino mine, concentrator, and smelter are located in Grant County in Southwestern New Mexico. Chino Mines Company is a partnership two-thirds owned and operated by Kennecott Santa Fe Corp., and one-third owned by MC Minerals Corp. (Mitsubishi) of Japan. The Chino Ore Body The Chino ore body is a widely varied deposit of rock types and contains intrusive stocks and sediments. The stocks contain chalcocite in a matrix of quartz, mica, and feldspar. Much of the feldspar is altered to clay. Some of these stocks are enriched with native copper. The sediments contain chalcopyrite associated with gangue minerals including magnetite, pyrite, garnet chlorite, and epidote. The contact of the stock and sediment is heavily altered to chlorite and clay. The stock ores contain economic quantities of molybdenite. The operating work index of Chino ore varies from 5 to 20 kwh/ton and averages 8.5 kwh/ton. The ore head to the concentrator averaged 0.81% copper and 0.010% molybdenum. Fifteen percent of the total copper head exists as nonsulfide mineralization.